Turismo colaborativo en Colombia: una realidad? - Yuneris Mu\~noz Cardona; Netty Consuelo Huertas; Stivenson Gómez Villegas (Atlantic Review of Economics (ARoEc), 2018)
– Although sharing is the essence of the human being, the emergence of the sharing economy is a recent phenomenon in the world, its growth has been boosted especially by the development of information technologies, which have served to connect users from different origins. The objective of this document was to conduct a tour of the sharing economy, how it has influenced the tourism sector, mainly in Colombia, a country that has grown in tourist numbers, mainly after the beginning of the process of peace dialogues. The results showed that the collaborative economy is based on trust between users and suppliers. This sharing has involved the emergence of a new business model called peer to peer P2P, which affects the tourism sector, thanks to the new consumer trends, among which is a change in the profile of tourists, who demand friendly products with the environment and have the need to be connected through social networks. The collaborative economy is a cultural phenomenon considered by the Times magazine as one of the ten ideas that will change the world, and that in Colombia just it begins.
Keywords: L8; L83; L86; O31; 330; Sharing economy; Technology Change; Tourism; Colombia. Economía colaborativa; Cambio tecnológico; Turismo; Colombia